2014
DOI: 10.1186/1749-8090-9-55
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective evaluation of fondaparinux for confirmed or suspected heparin-induced thrombocytopenia in left-ventricular-assist device patients

Abstract: BackgroundThrombotic events are a common complication of left ventricular assist device placement and warrant prophylactic anticoagulation. Heparin is the most common anticoagulant used for prophylaxis of thrombotic events in left ventricular assist device patients as a transition to oral anticoagulants but carries the risk of heparin-induced thrombocytopenia. Limited data is available for the treatment of heparin-induced thrombocytopenia in this patient population. We report an evaluation of 8 left ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The first step in treatment of HIT is to avoid heparin. Alternatives for anticoagulation include argatroban, bivalirudin, or fondaparinux . For patients with renal insufficiency, argatroban is the preferred choice.…”
Section: Clinical Hematologic Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first step in treatment of HIT is to avoid heparin. Alternatives for anticoagulation include argatroban, bivalirudin, or fondaparinux . For patients with renal insufficiency, argatroban is the preferred choice.…”
Section: Clinical Hematologic Manifestationsmentioning
confidence: 99%
“…Alternatives for anticoagulation include argatroban, bivalirudin, or fondaparinux. 63,64 For patients with renal insufficiency, argatroban is the preferred choice. Clearance of argatroban is decreased in hepatic disease, and the dose is typically decreased as well.…”
Section: Heparin-induced Thrombocytopeniamentioning
confidence: 99%
“…In this small study, 7 patients treated with fondaparinux showed similar rates of platelet recovery without new thrombosis as compared with historical controls treated with DTI. 48 Because increased bleeding rates (~10% to 22%) have been noted in small series, 49,50 caution must be exercised for use in critically-ill patients due to the drug's long half-life and renal clearance. British guidelines recommend the use of therapeutic dose fondaparinux for the management of HIT based on level 2C evidence.…”
Section: Fondaparinuxmentioning
confidence: 99%